2019
DOI: 10.1128/mra.01457-18
|View full text |Cite
|
Sign up to set email alerts
|

First Complete Genome Sequence of Human Coronavirus HKU1 from a Nonill Bat Guano Miner in Thailand

Abstract: Human coronavirus HKU1 (HCoV-HKU1) was first detected in a patient with viral pneumonia from Hong Kong in 2004. Here, we report the first complete genome sequence of HCoV-HKU1 from Thailand, obtained from a nonill person who worked in a bat cave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Second, most sequences in this study were obtained by consensus PCR using primers targeting highly conserved regions. Even if this broadly reactive PCR assay designed to detect widely variant CoVs has proven its ability to detect a large diversity of CoVs in a wide diversity of bats and mammals 30 , 74 77 , we may not rule out that some bat-CoV variants remained undetected. Using deep sequencing techniques would allow to detect this unknown and highly divergent diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, most sequences in this study were obtained by consensus PCR using primers targeting highly conserved regions. Even if this broadly reactive PCR assay designed to detect widely variant CoVs has proven its ability to detect a large diversity of CoVs in a wide diversity of bats and mammals 30 , 74 77 , we may not rule out that some bat-CoV variants remained undetected. Using deep sequencing techniques would allow to detect this unknown and highly divergent diversity.…”
Section: Discussionmentioning
confidence: 99%
“…An additional study, that directly supported the transmission of the coronaviruses to humans without the intervention of intermediate hosts, was performed by Wacharapluesadee et al 34 . They identified HKU1 betacoronavirus in guano of bats in Thailand, and detected its presence in a non-hill individual with high level of occupational exposure to guano.…”
Section: The Puzzle Of the Direct Spillovermentioning
confidence: 99%
“…They identified HKU1 betacoronavirus in guano of bats in Thailand, and detected its presence in a non-hill individual with high level of occupational exposure to guano. The authors of the study reported that the contamination of the individual with the HKU1 virus was likely to have occurred through a human-to-human transmission rather than through exposure to bats, underlining the high risk of zoonotic spillover to people collecting guano 34 .…”
Section: The Puzzle Of the Direct Spillovermentioning
confidence: 99%
“…HCoVs in Thai children were also found in a large multi-center, multi-country study of respiratory viruses and influenza-like illness, and while all four endemic viruses were detected across the study, there was no country specific breakdown of coronavirus species detected ( Taylor et al, 2017 ). Most recently, a HCoV-HKU1 virus was detected in a non-ill bat guano miner ( Joyjinda et al, 2019 ). All of these studies support the ongoing circulation of these HCoVs, and their association with respiratory illness.…”
Section: Endemic Human Coronaviruses In Thailandmentioning
confidence: 99%